Incremental Value of Live/Real Time Three‐Dimensional over Two‐Dimensional Transesophageal Echocardiography in the Assessment of Atrial Septal Pouch. (11th November 2015) - Elsayed, Mahmoud; Hsiung, Ming C.; Meggo‐Quiroz, L. David; Elguindy, Mostafa; Uygur, Begum; Tandon, Rohit; Guvenc, Tolga; Keser, Nurgul; Vural, Mustafa G.; Bulur, Serkan; Chahwala, Jugal R.; Abtahi, Firoozeh; et al.
Abstract : An atrial septal pouch (ASP) results from partial fusion of the septum primum and the septum secundum, and depending on the site of fusion, the pouch can be left‐sided (LASP) or right‐sided (RASP). LASPs have been described in association with thrombi found in patients admitted with acute strokes, raising awareness of its potential cardioembolic role, especially in those with no other clearly identifiable embolic source. We retrospectively studied 39 patients in whom the presence of an ASP had been identified by three‐dimensional transesophageal echocardiography (3DTEE) and who had a two‐dimensional transesophageal echocardiogram (2DTEE) performed during the same clinical encounter. The incremental value provided by 3DTEE over 2DTEE included the detection of six ASPs not found by 2DTEE; the detection of two ASPs in the same subject (in four patients) not identified by 2DTEE; larger ASP measurements of length and height in over 80% of the cases; and measurement of the ASP width (elevational axis) for the calculation of the area of the ASP opening, because of its unique capability to view the pouch en face. In addition, the volume of ASP and of the echogenic masses contained in the ASP (four of 39 patients) could be calculated by 3DTEE, which is a superior parameter of size characterization when compared to individual dimensions. One of these patients who presented with ischemic stroke diagnosed by magnetic resonance imaging had a large (>2 cm) mass in a LASP, with echolucencies similar to those seen in thrombi and associated with clot lysis and resolution. This mass completely disappeared on anticoagulant therapy lending credence that it was most likely a thrombus. There was no history of stroke or any other type of embolic event in the other three patients with masses in ASP. In conclusion, this retrospective study highlights the incremental value of 3DTEE over 2DTEE in the comprehensive assessment and characterization of ASPs, which can aid in the clarification of their role in cryptogenic stroke patients.